ADVENTURE TOURISM DEVELOPMENT PROGRAM FOR PREMIUM MARKET IN UJUNG KULON NATIONAL PARK - Raisya Shiva Rizal; Althofanis Juliheir Putra; Dwi Putri Nuraini; Fithriyah Fadhillah Ramadhani; Ni Made Jesthami Udgitha Prameswari; Zendra Haris Prasetya; Sumaryadi; Sugeng Hermanto (Politeknik Pariwisata NHI Bandung, 2023)
Ujung Kulon National Park (TNUK) has their uniqueness in the diversity of flora and fauna. Thus, it becomes one of the priorities of the Ministry of Tourism and Creative Economy as a tourism development destination, with the availability of adventure tourism products that are being in line with the expectations of the premium market, we called it authentic and exclusive products. The result of this research is to produce an integrated program plan to develop adventure tourism in TNUK which targeting a premium market tourist. The method that we used in this research is descriptive, which suitable to explain the actual situation of TNUK tourism. And to make it more relevant, the collected data were analyzed using descriptive statistical analysis. In results, showed that the development of adventure tourism in TNUK met the dimensions of adventure tourism, as follows; natural environment, physical activity, cultural immersion, risk & competence, operators, and sustainability. However, the characteristics in unqualified of the premium market. Hence, It is necessary to apply the concept of quality tourism